ANALISIS PENGGUNAAN KALIMAT MAJEMUK DALAM DETIKNEWS.COM DAN IMPLIKASINYA DALAM PEMBELAJARAN DI SMA - Heri Sabarno; Afrinar Pramitasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Compound sentences constitute one of the linguistic features frequently employed in news articles to present information in a coherent, systematic, and effective manner. This study aims to describe the forms of compound sentences found in news articles published on Detiknews.com and to examine their implications for Indonesian language learning at the senior high school level. This research employed a descriptive qualitative approach using the interactive model of data analysis. The findings revealed that, based on the analysis of six news articles, a total of 20 compound sentence constructions were identified, consisting of 11 coordinate compound sentences, 8 subordinate compound sentences, and 1 mixed compound sentence. Coordinate compound sentences were predominantly characterized by additive and adversative relationships, while subordinate compound sentences exhibited temporal, causal, result, purposive, complement, and restrictive attributive relationships. The mixed compound sentence combined both coordinate and subordinate clause relationships within a single sentence construction. The findings have pedagogical implications for Indonesian language instruction in senior high schools, as they may serve as contextual teaching materials to support students in understanding various forms of compound sentences through authentic news texts. Keywords: Compound Sentences, Compound Sentence Forms, Detiknews.com